High sensitivity C-reactive protein is associated with vulnerable characteristics in non-culprit plaques in patients with ST-segment elevation myocardial infarction. (4th February 2022) - Katamine, M; Minami, Y; Nagata, T; Asakura, K; Katsura, A; Kinoshita, D; Hashimoto, T; Ako, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Higher level of high sensitivity C-reactive protein (hsCRP) is associated with an increased risk of recurrent cardiovascular events in patients with ST-segment elevation myocardial infarction (STEMI). However, the association between hsCRP and the characteristics of non-culprit plaques in patients with STEMI remains to be elucidated. Purpose: To clarify the morphological characteristics of non-culprit plaque in patients with STEMI according to the hsCRP levels using optical coherence tomography (OCT). Methods: A total of 79 non-culprit plaques in 76 consecutive patients with STEMI, who underwent OCT imaging of the non-culprit plaques in a culprit vessel were included. The characteristics of non-culprit plaques assessed by OCT were compared between the higher hsCRP group (hsCRP ≥ 0.16 mg/dL, 38 plaques in 38 patients) and the lower hsCRP group (hsCRP < 0.16 mg/dL, 41 plaques in 38 patients). Results: The prevalence of plaque with macrophage (63.2 vs. 31.7%, p = 0.006), plaque with large lipid (maximal lipid arc > 180 °) (57.9 vs. 31.7%, p = 0.018), healed plaque (50.0 vs. 26.8%, p = 0.045) and cholesterol crystal (18.4 vs. 2.4%, p = 0.045) was significantly higher in the higher hsCRP group than in the lower hsCRP group (Figure). In a multivariate analysis, the higher hsCRP was independently associated with the presence of plaque with macrophage (Odds ratio [OR], 3.031; 95% confidence interval [CI]: 1.112-8.264, p = 0.030), plaque with large lipid (OR, 2.897; 95% CI: 1.122-7.478, p = 0.026) and healed plaque (OR, 2.666; 95% CI: 1.030-6.896, p = 0.040). Conclusions: Higher level of hsCRP is associated with a higher prevalence of vulnerable characteristics in non-culprit plaques in patients with STEMI. The present results may partly explain the pathogenesis of an increased incidence of recurrent cardiovascular events in patients with STEMI.